Dawah Islam dengan pembangunan masyarakat desa - Suryadi, A. (Bandung : Mandar Maju, 1989)
Islamic propagation related to rural development in Indonesia.
Includes bibliographical references (p. 285-286)
Keywords: Community development -- Indonesia; Islam -- Missions -- Indonesia; Da'wah (Islam)